Molecular circumscription and major evolutionary lineages of the fern genus Dryopteris (Dryopteridaceae) - Zhang Li-Bing; Zhang Liang; Dong Shi-Yong; Sessa Emily B; Gao Xin-Fen; Ebihara Atsushi (BMC Evolutionary Biology, 2012)
Abstract Background The fern genus Dryopteris (Dryopteridaceae) is among the most common and species rich fern genera in temperate forests in the northern hemisphere containing 225–300 species worldwide. The circumscription of Dryopteris has been controversial and various related genera have, over the time, been included in and excluded from Dryopteris. The infrageneric phylogeny has largely remained unclear, and the placement of the majority of the supraspecific taxa of Dryopteris has never been tested using molecular data. Results In this study, DNA sequences of four plastid loci (rbcL gene, rps4-trnS spacer, trnL intron, trnL-F spacer) were used to reconstruct the phylogeny of Dryopteris. A total of 122 accessions are sampled in our analysis and they represent 100 species of the expanded Dryopteris including Acrophorus, Acrorumohra, Diacalpe, Dryopsis, Nothoperanema, and Peranema. All four subgenera and 19 sections currently recognized in Dryopteris s.s. are included. One species each of Arachniodes, Leptorumohra, and Lithostegia of Dryopteridaceae are used as outgroups. Our study confirms the paraphyly of Dryopteris and provides the first strong molecular evidence on the monophyly of Acrophorus, Diacalpe, Dryopsis, Nothoperanema, and Peranema. However, all these monophyletic groups together with the paraphyletic Acrorumohra are suggested to be merged into Dryopteris based on both molecular and morphological evidence. Our analysis identified 13 well-supported monophyletic groups. Each of the 13 clades is additionally supported by morphological synapomophies and is inferred to represent a major evolutionary lineage in Dryopteris. In contrast, monophyly of the four subgenera and 15 out of 19 sections currently recognized in Dryopteris s.s is not supported by plastid data. Conclusions The genera, Acrophorus, Acrorumohra, Diacalpe, Dryopsis, Nothoperanema, and Peranema, should all be merged into Dryopteris. Most species of these genera share a short rhizome and catadromic arrangement of frond segments, unlike the sister genus of Dryopteris s.l., Arachniodes, which has anadromic arrangement of frond segments. The non-monophyly of the 19 out of the 21 supraspecific taxa (sections, subgenera) in Dryopteris strongly suggests that the current taxonomy of this genus is in need of revision. The disagreement between the previous taxonomy and molecular results in Dryopteris may be due partly to interspecific hybridization and polyplodization. More morphological studies and molecular data, especially from the nuclear genome, are needed to thoroughly elucidate the evolutionary history of Dryopteris. The 13 well-supported clades identified based on our data represent 13 major evolutionary lineages in Dryopteris that are also supported by morphological synapomophies.